PEMBERIAN PUPUK KANDANG YANG BERBEDA TERHADAP PERTUMBUHAN RUMPUT GAJAH MINI (Pennisteum purpureum CV. Mott) - Sadi, Ristasari (Program Studi Peternakan Universitas Muhammadiyah Sidenreng Rappang, 2025)
The purpose of this study was to determine the application of different manure to the growth of Mini Elephant Grass. This study used the Randomized Block Design (RAK) method with 4 treatments and repeated 4 times so that 16 experimental units were obtained. The treatments of this study were P0: without application of manure, P1: cow manure 910 tons/ha), P2: goat manure 915 tons/ha), P3: chicken manure (20 tons/ha). The parameters measured in this study were plant height, leaf length, number of shoots and fresh weight of Mini Elephant Grass. The results showed that the application of different manure significantly differed (P <0.05) on the number of shoots and fresh weight of Mini Elephant Grass. While for plant height and leaf length showed no difference (P> 0.05). The application of different manure can increase the growth of Mini Elephant Grass consisting of plant height, leaf length, number of shoots and fresh weight. The application of chicken manure (P3) is the best treatment to increase the growth of Mini Elephant Grass.